Analysis of Factors Driving Purchase Intention of Electric Cars: Perspective of Theory of Planned Behavior, Norm Activation Model, and Technology Acceptance Model - Handarujati, Enggar (Cv. Syntax Corporation Indonesia, 2024)
Objective: The purpose of this study is to empirically investigate the factors that drive the purchase intention of electric cars from the perspective of the Theory of Planned Behavior (TPB), Norm Activation Model (NAM), and Technology Acceptance Model (TAM). Design/Methods/Approach: This study used quantitative research methods with purposive sampling. The data collection method used in this research is the survey method, conducted using a questionnaire distributed online using Google Forms to 253 respondents who do not own an electric car, have a driver’s license, belong to Socioeconomic Status A group, and have knowledge related to electric cars.. A 49-item questionnaire was developed, with a five-point Likert scale on each item. This study used partial least square structural equation modeling (PLS-SEM) for data analysis. Data were analyzed using Smart-PLS 3.2.9 application. Findings: Perceived Usefulness (PU) and Perceived Behavioral Control (PBC) positively and significantly impact the intention to purchase electric cars. Originality/Value: This study contributes to the existing literature on the purchase intention of electric cars by combining three theories namely TPB, NAM, and TAM. Practical/Policy implication: Given the results, government and manufacturers of electric cars in Indonesia should focus the strategies in the area of the usefulness of electric cars and consumers’ perceived behavioral control to increase the purchase intention of electric cars.